Chupacabra - Smith, Roland, 1951- (Scholastic Press, 2013)
Marty and his uncle, cryptozoologist Travis Wolfe, search the world for Grace, Wolfe's daughter, after she is kidnapped by her grandfather, and, to make matters worse, a chupacabra has been sighted, putting them both in danger of coming face-to-face with the mythic monster.